Epidemiology of SARS-CoV-2: numbers matter! - Casti, Giorgia; Bassareo, Pier Paolo; Limone, Marco; Pistolesi, Filippo; Fanos, Vassilios; Marcialis, Maria Antonietta (Journal of Pediatric and Neonatal Individualized Medicine (JPNIM), 2020)
The ongoing pandemic is the result of the spread of a recently identified Coronavirus, named SARS-CoV-2 (Severe Acute Respiratory Syndrome – Coronavirus – 2). Since 31th December 2019, when the first cluster was reported in Wuhan (China), the global Novel COronaVIrus Disease 2019 (COVID-19) cases significantly increased, and on 12th March 2020, the WHO Director declared the disease as pandemic. As of April 28th 2020, 2.982,688 cases and 210,193 deaths were reported globally. The aim of this article is the analysis of the main epidemiological characteristics of the current pandemic: transmission, basic reproduction number (R0), incubation period, global, European and Italian confirmed cases and deaths, focusing on the paediatric population.